THE FEATURES OF AESTHETIC EDUCATION FOR THE DEVELOPMENT OF VISUAL LANGUAGE OF ARCHITECTURE STUDENTS - HADJI-BANDALAC, Mariana (Journal of Social Sciences, 2023)
This work emphasizes some theoretical and practical provisions of aesthetic education, which have an important role in the development of visual language of architecture students. The principle of integrating scientific knowledge and creative skills ensures the success of the architecture student, valuing language as a tool used in free expression. One of the solutions refers to the analysis of the architectural context and project development based on visual language skills, and brainstorming, an idea-generating activity, can be taken as a method. Another solution would be to encourage students to take responsibility for the transmission of visual language from the perspective of aesthetic values. Taking on the role of a future architect by developing analytical skills and conveying aesthetic values, the student gains experience in modelling space and effectively conveying visual images of architectural edifices.